The use of Direct-Acting Antivirals in Hepatitis C Virus-Infected Patients with Hepatocellular Carcinoma. (4th October 2017) - Economides, Minas; Hosry, Jeff; Angelidakis, Georgios; Kaseb, Ahmed; Torres, Harrys
Abstract: Background: Hepatitis C virus (HCV)-infected patients with hepatocellular carcinoma (HCC) are at high risk for direct-acting antiviral (DAA) failure and controversy exists on the increased risk of HCC recurrence following DAAs. Herein, we evaluate the efficacy, safety and oncologic outcomes of HCV-infected patients with HCC treated with DAAs. Methods: This prospective observational study included consecutive patients seen at MD Anderson Cancer Center (January 2014–April 2017). Patients received 1 out of 5 different combinations. Efficacy was assessed by intention-to-treat (ITT) analysis based on sustained virological response 12 weeks after finishing DAAs (SVR12). Adverse events (AEs) and clinically significant drug-drug interactions (DDIs) were analyzed. AEs were graded according to the Division of AIDS Table (v 2.0). Cancer response was evaluated at the time of initiation and 6 months after finishing DAAs. Results: Twenty-seven patients were enrolled. The majority were men (85%), white (55%) with genotype 1 HCV (66%), Child-Pugh score A (85%), tumor stage 4 (41%) and eligible for potentially curative options (74%). The SVR12 (ITT) data are depicted in table. The most common AEs were headache (11%) and anemia (7%). Only one pt had grade 3 AE (renal failure) but grade 4 AEs or DDIs were not observed. Among patients with potentially curable HCC ( n = 20), the disease control rate was 35% (complete remission 10%, partial remission 25%) with recurrence rate of 5% (1 pt). None of the patients had de novo HCC within 6 months of DAAs. All 7 patients with unresectable HCC had stable disease within 6 months of DAAs. Conclusion: DAAs appear to be safe but of suboptimal efficacy in HCV-infected patients with HCC. More studies are needed to identify the subset of patients who will benefit from DAAs. Disclosures: H. Torres, Gilead Sciences: Consultant and Grant Investigator, Consulting fee, Grant recipient and Research support. Merck & Co: Consultant and Grant Investigator, Consulting fee and Grant recipient. Janssen Pharmaceuticals, Inc.: Consultant, Consulting fee. Dynavax Technologies: Consultant, Consulting fee